2015
DOI: 10.5144/0256-4947.2015.359
|View full text |Cite
|
Sign up to set email alerts
|

Psychiatric disorders among infertile men and women attending three infertility clinics in Riyadh, Saudi Arabia

Abstract: BACKGROUND AND OBJECTIVESNo study has assessed psychiatric disorders among infertile men and women seeking fertility treatment in Saudi Arabia. Therefore, we sought to measure the rate of psychiatric disorders in this population.DESIGN AND SETTINGSThis was a cross-sectional observational study among patients attending infertility clinics at three referral hospitals in Riyadh, Saudi Arabia, between January 2013 and September 2014.PATIENTS AND METHODS406 patients (206 women and 200 men) participated in the study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 36 publications
2
13
1
Order By: Relevance
“…A study done in Saudi Arabia also mentioned that depression (26.2%) was more prevalent than the anxiety disorder (22%) in infertile female subjects, and the rates are similar to those of our study. [ 28 ] Suicidal ideas were present in 16% in our study, which was similar to the study finding of Alosaimi et al . [ 28 ] who reported around 17%.…”
Section: Discussionsupporting
confidence: 92%
“…A study done in Saudi Arabia also mentioned that depression (26.2%) was more prevalent than the anxiety disorder (22%) in infertile female subjects, and the rates are similar to those of our study. [ 28 ] Suicidal ideas were present in 16% in our study, which was similar to the study finding of Alosaimi et al . [ 28 ] who reported around 17%.…”
Section: Discussionsupporting
confidence: 92%
“…Global reports indicated differences in the prevalence of anxiety in infertile couples [21] as infertile women experience a higher level of anxiety than that experienced by infertile men, and the inability to conceive affects anxiety prevalence among the former [22]. The diversity in findings is reflected, for example, in the works of Alosaimi et al [23], Maroufizadeh et al [24], and Volgsten et al [25], who found that anxiety prevalence among infertile women in Saudi Arabia, Iran, and Sweden reached rates of 21.8, 58.1, and 14.8%, respectively. Despite the value presented by these studies, however, no metaanalytic research has been devoted to specifically outlining anxiety prevalence with regard to female factors.…”
Section: Introductionmentioning
confidence: 99%
“…These findings are similar with previous studies reported by Abolfotouh et al, (2013) that showed that most of the infertile and fertile males had moderate level of socio-economic status. Other studies reported by Sahraian et al, 2016;Alosaimi et al, 2015;Wang et al, 2015;Ahmadi et al, (2011) stated that majority of the infertile males had moderate level of socio-economic status. While, these findings were not supported by Zhang, 2016;Yusuf et al, 2012& Gulec et al, (2011 who found that most of the infertile males showed low level of socio-economic status.…”
Section: Discussionmentioning
confidence: 90%